A Novel de novo Mutation in EBF3 Associated With Hypotonia, Ataxia, and Delayed Development Syndrome in a Chinese Boy - Huang, Yanru; Mei, Libin; Wang, Yangdan; Ye, Huiming; Ma, Xiaomin; Zhang, Jian; Cai, Meijiao; Li, Ping; Ge, Yunsheng; Zhou, Yulin (Frontiers in Genetics, 2021)
Global developmental delay has markedly high phenotypic and genetic heterogeneity, and is a great challenge for clinical diagnosis. Hypotonia, ataxia, and delayed development syndrome (HADDS), first reported in 2017, is one type of global development delay. Here, we investigated the genetic etiology of a Chinese boy with global developmental delay. We combined clinical and imaging phenotyping with trio whole-exome sequencing and Sanger sequencing to the patient and his clinically unaffected parents. A luciferase reporter and immunofluorescence were performed to detect the effect of mutation on transcriptional activity and subcellular localization. The patient presented with several previously unreported symptoms in the patients with HADDS, including hemangiomas, mild hearing abnormalities and tracheomalacia. A novel EBF3 c.589A>G missense mutation (p.Asn197Asp, p.N197D) was identified in the patient. By constructing the plasmid and transfecting HEK293T cells, EBF3-N197D mutant showed impaired activation of luciferase reporter expression of the p21 promoter, and the mutant affected its entry into the nucleus. To our knowledge, this is the first report of EBF3 pathogenic mutation which associated with HADDS in the Chinese population. Our results expand the phenotypes and pathogenic mutation spectrum of HADDS, thus potentially facilitating the clinical diagnosis and genetic counseling of HADDS patients.